The Optimal Chinese Herbal Injections for Use With Radiotherapy to Treat Esophageal Cancer: A Systematic Review and Bayesian Network Meta-Analysis - Dan Zhang; Mengwei Ni; Jiarui Wu; Shuyu Liu; Ziqi Meng; Jinhui Tian; Xiaomeng Zhang; Bing Zhang (Frontiers Media S.A., 2019)
Ethnopharmacological relevance: Esophageal cancer is one of the most common human cancers, and its incidence is highly endemic in China. The combination of Chinese herbal injections (CHIs) and radiotherapy should be informed by the best available evidence.Aim of the study: To update and expand on previous work in order to compare and rank the efficacy and safety of CHIs in combination with radiotherapy to treat esophageal cancer.Materials and Methods: We searched several electronic databases to identify randomized controlled trials (RCTs) regarding CHIs to treat esophageal cancer from their inception to March 15, 2017. In a network meta-analysis (NMA), the bias of the included trials was assessed by two individuals independently in accordance with the Cochrane Handbook for Systematic Reviews of Interventions. Outcomes such as the clinical effectiveness rate, performance status, adverse reactions (ADRs), and survival rate were evaluated. We performed a random-effects NMA to obtain estimates of efficacy and safety outcomes, and we present these estimates as odds ratios (ORs) and corresponding 95% confidence intervals (CIs) calculated via Stata 13.1 and WinBUGS 1.4 software. Furthermore, the surface under cumulative the ranking curve (SUCRA) was used to rank the efficacy and safety of different CHIs in relation to each outcome.Results: Of 685 identified trials, 55 were eligible for inclusion in the study. These 55 trials included 12 CHIs and 4,114 participants. The cluster analysis results suggested that Compound kushen injection therapy is the optimal CHI treatment for patients with esophageal cancer in terms of improving the clinical effectiveness rate and performance status. Huachansu and Kangai injection are superior in improving 1-year and 2-year survival rates. Lentinan injection may be considered a favorable choice for reliving ADRs, and Compound kushen injection may provide treatment benefits by reducing both gastrointestinal reaction and radiation esophagitis.Conclusions: The current clinical evidence indicated that Compound kushen injection combined with radiotherapy is the most preferable and beneficial option for patients with esophageal cancer in terms of efficacy and safety. However, the results of our study should be interpreted with caution given the limitations of the sample size and the methodological quality of the included trials.